(untitled) (Revista Lusófona de Educação, 2020)
In the ambit of higher education internationalization, Portuguese universities have been receiving an increasing number of students from Portuguese-Speaking countries (CPLP), namely at the level of Ph.D. studies that pose questions related to the intercultural dimension of doctoral supervision. Research in Portugal concerning this issue is scarce and this paper focused on Ph.D. students from the CPLP and their supervisors in the Department of Education and Psychology of the University of Aveiro, intends to answer the following questions: in the situation of intercultural doctoral supervision in which both students and supervisors are engaged, what cultural encounters occur? Are these encounters productive or problematic? Semi-structured interviews were conducted with twelve students and eight supervisors. Results from thematic analysis indicate that different cultural encounters do occur between pedagogical/academic cultures; linguistic backgrounds; research and knowledge cultures and communication/relational cultures. Both students and supervisors acknowledge that these encounters bring about potentials (productive view) and constraints (problematic view) which will be discussed. Keywords: intercultural doctoral supervision; Portuguese higher education; students from Portuguese-speaking countries